Xanthine oxidoreductase activity is correlated with hepatic steatosis - Chisako Yagi; Yoshiki Kusunoki; Taku Tsunoda; Takayo Murase; Takashi Nakamura; Keiko Osugi; Mana Ohigashi; Akiko Morimoto; Akio Miyoshi; Miki Kakutani-Hatayama; Kae Kosaka-Hamamoto; Manabu Kadoya; et al. (Scientific Reports, 2022)
Abstract The enzyme xanthine oxidoreductase (XOR) catalyzes the synthesis of uric acid (UA) from hypoxanthine and xanthine, which are products of purine metabolism starting from ribose-5-phosphate. Several studies suggested a relationship between hyperuricemia and hepatic steatosis; however, few previous studies have directly examined the relationship between XOR activity and hepatic steatosis. A total of 223 subjects with one or more cardiovascular risk factors were enrolled. The liver-to-spleen (L/S) ratio on computed tomography and the hepatic steatosis index (HSI) were used to assess hepatic steatosis. We used a newly developed highly sensitive assay based on [13C2, 15N2] xanthine and liquid chromatography/triple quadrupole mass spectrometry to measure plasma XOR activity. Subjects with the L/S ratio of < 1.1 and the HSI of < 36 had increased XOR activity and serum UA levels. Independent of insulin resistance and serum UA levels, multivariate logistic regression analysis revealed that plasma XOR activity was associated with the risk of hepatic steatosis as assessed by the L/S ratio and HSI. According to the findings of this study, plasma XOR activity is associated with hepatic steatosis independent of insulin resistance and serum UA levels.